Exploring the impact of user-generated content and tourist satisfaction on destination loyalty in China’s ethnic tourism: The moderating role of cultural intelligence - Huang, Xiaoxu; Chelliah, Shankar (International Journal of Management and Sustainability, 2025)
This study explores the impact of user-generated content (UGC) and tourist satisfaction on destination loyalty in ethnic tourism through the theory of planned behavior (TPB) and examines the moderating role of cultural intelligence in this process. Ethnic tourism attracts tourists seeking cultural diversity and authenticity through its unique customs and traditions. The surge of UGC on social media is altering and reshaping tourist behavior, posing new challenges for ethnic tourism destinations in fostering loyalty. This quantitative study collected data from a survey of 328 tourists who had visited ethnic tourism destinations. The results show that UGC and tourist satisfaction positively impact destination loyalty, with the latter having a more significant effect. Additionally, UGC positively affects tourist satisfaction, which underscores the impact of social factors on individual perceptions and evaluations when consuming tourism products that cannot be experienced in advance and are characterized by uncertainty. The study also shows that cultural intelligence has a positive moderating effect on the relationship between tourist satisfaction and destination loyalty. This shows how important it is to have cultural intelligence when dealing with cultural shock. This study deepens the comprehension of destination loyalty and offers valuable insights into the sustainable development of ethnic tourism.